Estudo de análise de vulnerabilidade em uma ampliação de área de armazenamento de produtos químicos inflamáveis - Pereira, Alessandra Baum (Universidade do Vale do Rio dos Sinos, 2023)
The article presents a vulnerability analysis applied to the expansion of a storage area for flammable chemicals. The application of the analysis is a mandatory condition for granting an operational license, following the regulations of FEPAM (a government agency in the state of Rio Grande do Sul that regulates, manages and issues legal licenses). The process was applied in a real company, a petrochemical industry in the same state. The study followed the entire sequence of activities in the FEPAM Risk Analysis Manual. As a result, 23 scenarios were analyzed and the two most critical were presented in detail, using computer simulations to bring a quantified impact on the site and in the neighborhood. The results show that even the most serious scenarios do not pose relevant risks to workers and the local community, and the factory can continue with the license and operate in the area.
Keywords: Segurança de processo; Vulnerabilidade; Manual de análise de riscos ambientais; Process safety; Risk analysis; Vulnerability; Guideline for environmental risk analysis; Análise de riscos